Just War and Human Rights Fighting with Right Intention - Burkhardt, Todd (SUNY Press Open Access, 2017)
Warfare in the twenty-first century presents significant challenges to the modern state. Serious questions have arisen about the use of drones, target selection, civilian exposure to harm, intervening for humanitarian reasons, and war as a means of forcing regime change. In Just War and Human Rights Todd Burkhardt argues that updating the laws of war and reforming just war theory is needed. A twenty-year veteran of the US Army, Burkhardt claims that war is impermissible unless it is engaged, fought, and concluded with right intention. A state must not only have a just cause and limit its war-making activity in order to vindicate the just cause, but it must also seek to vindicate its just cause in a way that yields a just and lasting peace. A just and lasting peace is motivated by the just war tenet of right intention and predicated on the realization of human rights. Therefore, human rights should not only dictate how a state treats its own people but also how a state treats the people of other countries, insulating them and protecting innocent civilians from the harms of war.